3D research challenges in cultural heritage II : how to manage data and knowledge related to interpretative digital 3D reconstructions of cultural heritage /: how to manage data and knowledge related to interpretative digital 3D reconstructions of cultural heritage. (2016) - Unknown
No abstract available